CHRISTIAN EDUCATORS' MENTAL HEALTH CONDITION AND WELL-BEING IN INDONESIA DURING THE COVID-19 PANDEMIC - Rianti Setiadi; Sarinah Lo; Bobby Wiryawan Saputra (Universitas Pelita Harapan, 2022)
This descriptive quantitative study aims to explore Christian educators' mental health condition and well-being in Indonesia during the Covid-19 pandemic. Data collection was carried out from March 30 to April 24, 2021. The participants of this study are Christian educators who either teach at Christian, public, or national private schools. The findings show that Christian educators in Indonesia have a high vocational passion (89%), good mental health (97.6%), high level of spiritual well-being (94.8%), relatively good social well-being (82, 8%), economic well-being is quite good (79.4%). In comparison, only 52.8% participants who have high health well-being and 66% who has high life satisfaction. The chisquare test shows that the components of well-being (spiritual, economic, social, and health) significantly affect the level of mental health of educators. The main challenges faced by educators are learning to support technology; teaching and learning activities that are deemed not optimal; attitudes and behavior of students who are less disciplined, polite, cooperative, and motivated; lack of relationships and interactions between teachers and teachers as well as fellow students; and increased workloads and hours leading to physical and mental health exhaustion. The main implication is for the decisionmakers of Christian educational institutions in Indonesia to pay special attention to the health well-being of educators who have experienced physical exhaustion by evaluating and adjusting the expectations and workloads, and developing a well-being ecosystem at school.Bahasa Indonesia Abstrak: Penelitian kuantitatif deskriptif ini bertujuan untuk mengetahui kondisi kesehatan mental dan well-being pendidik Kristen di Indonesia selama masa pandemic Covid-19. Pengambilan data dilakukan pada 30 Maret sampai dengan 24 April 2021. Peserta penelitian ini adalah pendidik Kristen yang mengajar di sekolah Kristen, negeri, atau swasta nasional. Hasil temuan menunjukkan pendidik Kristen di Indonesia memiliki vocational passion yang tinggi (89%), kesehatan mental yang baik (97,6%), tingkat well-being spiritual tinggi (94,8%), well-being sosial relatif baik (82,8%), well-being ekonomi cukup baik (79,4%), sedangkan well-being kesehatan hanya 52,8% yang tinggi. Sebanyak 66% pendidik memiliki kepuasan hidup yang tinggi. Uji chi square menunjukkan bahwa komponen well-being (spiritual, ekonomi, sosial, dan kesehatan) mempunyai hubungan yang signifikan dengan tingkat kesehatan mental para pendidik. Tantangan utama yang dihadapi pendidik adalah masalah: teknologi pendukung pembelajaran; kegiatan belajar mengajar yang dirasa tidak maksimal; sikap dan perilaku murid yang kurang disiplin, sopan, kooperatif, dan motivasi; kurangnya relasi dan interaksi antara guru dan guru serta sesama murid; dan beban dan jam kerja yang bertambah yang menyebabkan kelelahan kesehatan fisik dan mental. Implikasi utama dari temuan ini bagi para pengambil keputusan lembaga pendidikan Kristen di Indonesia untuk memberikan perhatian khusus well-being kesehatan dari para pendidik yang telah mengalami kelelahan fisik dengan mengevaluasi dan menyesuaikan ekspektasi, beban kerja, dan jam kerja yang jelas dan membangun ekosistem well-being di sekolah.